Perceived body image of female college students - Almonte, Darby April Gaye Quioyo
The study aims to describe the perceived body image of female college students. Specifically, it wants to find out the activities of female college students relative to their body image, their exposure to the mass media in terms of enhancing body image; and to find out the influence of mass media exposure to their perceived body image. The study was conducted in the College of Arts and Sciences, University of the Philippines in the Visayas, Miag-ao. Sixty respondents were obtained from the population of Social Sciences students using the fishbowl method of simple random sampling. The Body parts Satisfaction Scale (Spainhour, 2000), together with a set of questions developed by the researchers, wer used in gathering the data. Generally, the results showed that the femalecollege students have a postive perception of their body image. Also, the female college students do not engage in any activity related to body image, such as dieting and exercising. Lastly, they are well exposed to the mass mediated messages about body image in the television and the magazine but they are not negatively influenced by those messages, that is, they neither compare their bodies with nor they want to look like the models in television and magazine.